Confocal Raman microscopy combined with optical clearing for identification of inks in multicolored tattooed skin: In vivo - Darvin, Maxim E.; Schleusener, Johannes; Parenz, Franziska; Seidel, Olaf; Krafft, Christoph; Popp, Juergen; Lademann, Juergen (Analyst, 2018)
Raman measurements applied on freshly tattooed porcine skin ex vivo showed a possibility of obtaining the ink pigment related information in the skin. Based on these results, confocal Raman microscopy was used to identify the tattoo ink pigments of different colors in multicolored tattooed human skin in vivo. The Raman signatures of tattoo ink pigments were unique. Therefore, it could be shown that the applied method is successful for the identification of the tattoo ink pigments in human skin in vivo down to depths of approx. 50 μm, which is sufficient to screen the entire epidermis and the top of the papillary dermis area on the forearm and leg skin sites. Additional application of the optical clearing technique in vivo by topical application of glycerol, combined with tape stripping removal of the uppermost stratum corneum layers and defatting allows the extension of depths of investigation in tattooed skin down to approx. 400 μm, i.e. to cover the entire papillary dermis and a large part of the reticular dermis. Thus, the tattoo ink pigments were identified in vivo and depth-dependently in human tattooed skin confirming their presence in the papillary and reticular dermis. The proposed non-invasive in vivo Raman screening combined with optical clearing for identifying the tattoo pigments in the dermis can be an important task preceding a laser-based tattoo removal procedure and for determining the optimal laser parameters.
CRIS-Team Scopus Importer:2023-04-20